The Role of Social Media In Startup Market Research And Intelligence - Mishra, Biswo Ranjan; Gnanasekaran, G.; Dwivedi, Anshu; Mallick, Rwitabrata; Kumar, K. Suresh; Kavipriya, N. (Journal of Neonatal Surgery, 2025)
In the dynamic and competitive business environment, startups must rely on efficient, cost-effective methods for market research and intelligence. Social media has emerged as a transformative tool, enabling startups to gather real-time data, understand consumer behavior, track competitors, and make informed decisions. This research paper explores how startups leverage social media platforms for market research and competitive intelligence. It delves into methodologies such as sentiment analysis, social listening, trend forecasting, and audience analytics, providing real-world examples and data to support these functions. The study also examines the challenges startups face when using social media for research, including data privacy, information overload, and authenticity of insights. The paper concludes by highlighting best practices and offering recommendations for startups aiming to harness the full potential of social media as a strategic asset in market intelligence.